2018
DOI: 10.1371/journal.pone.0205387
|View full text |Cite
|
Sign up to set email alerts
|

DeepFocus: Detection of out-of-focus regions in whole slide digital images using deep learning

Abstract: The development of whole slide scanners has revolutionized the field of digital pathology. Unfortunately, whole slide scanners often produce images with out-of-focus/blurry areas that limit the amount of tissue available for a pathologist to make accurate diagnosis/prognosis. Moreover, these artifacts hamper the performance of computerized image analysis systems. These areas are typically identified by visual inspection, which leads to a subjective evaluation causing high intra- and inter-observer variability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 20 publications
0
95
0
Order By: Relevance
“…Previous reports indicated that the computational analysis of H&E images assists pathological diagnosis. 12,13 We also showed that wndchrm recapitulated pathological decisions, since the algorithm achieved acceptable classification | 2231 YASUDA et Al performance using H&E images of gastric cancers with distinct histological grades (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous reports indicated that the computational analysis of H&E images assists pathological diagnosis. 12,13 We also showed that wndchrm recapitulated pathological decisions, since the algorithm achieved acceptable classification | 2231 YASUDA et Al performance using H&E images of gastric cancers with distinct histological grades (Figure 1).…”
Section: Discussionmentioning
confidence: 75%
“…Characteristics of cancerous tissues derived from patients provides diagnostic information regarding the tumors, and allows prediction of therapeutic responses and prognosis . Pathological assessment of cancer specimens stained with hematoxylin and eosin (H&E) is primarily interpreted not only by tissue architecture but also by nuclear morphology of the tumor cells, which has been used for routine clinical diagnosis and computer‐aided pathological diagnosis . Recently, this field has significantly progressed to decipher clinical and biological relevance from such pathological images by combining molecular information such as genomic data …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning and deep learning methods have also been used for quality assessment in whole slide images. Senaras et al [38] applied deep learning methods to detect out-of-focus regions in whole slide tissue images that can be avoided in segmentation and classification operations. Wen et al [39,40] utilized machine learning classifiers (SVM, random forest, and CNN) that operate on texture and intensity features extracted from image patches to evaluate the quality of nuclear segmentation results.…”
Section: Image Analysis Tasks and Machine Learningmentioning
confidence: 99%
“…In addition to these variations, deep learning algorithms can also be sensitive to image artifacts. Some research has attempted to account for these issues by detecting and pre-screening image artifacts, either by automatically [37][38][39] or manually removing slides with artifacts 19,25,31 . The recent work of Campanella et al made substantial progress towards validating a deep learning system on data completely free of curation 25 .…”
mentioning
confidence: 99%